THE EFFECT OFTHE LOCALLY - GENERATED REVENUE AND THE GENERAL ALLOCATION FUND ON THE CAPITAL EXPENDITURE (Survey On the Provincial /District / City Region Banten and DKI Jakarta) - Hari Setiyawati (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2016)
The purpose of this study was to see whether there is an influence of The Locally-Generated Revenue and The General Allocation Fund on the Capital Expenditure . The Locally-Generated Revenue is measured from the taxes, levies, wealth management outcomes separated areas and other legitimate LocallyGenerated Revenue. The General Allocation Fund is measured from domestic revenue, the fiscal gap and basic allocation. The Capital Expenditure is property, plant and equipment expenditures. This study is a survey research in provincial government / district / city of Banten and Jakarta. The sample in this study were all local governments in the two provinces, amounting to ten local governments, so this study is a census research, in the sense that the entire population sampled. Data analysis method used is the multiple regression. From the results of data analysis and discussion, it can be concluded that The Locally-Generated Revenue affect on the Capital Expenditure. The General Allocation Fund affect on the Capital Expenditure.